2012
DOI: 10.1155/2012/982683
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes in theCRPGene Associated with Increased BMI and Levels of CRP in Subjects with Type 2 Diabetes or Obesity from Southwestern Mexico

Abstract: Objective. We evaluated the association between four polymorphisms in the CRP gene with circulating levels of C-reactive protein (CRP), type 2 diabetes (T2D), obesity, and risk score of coronary heart disease. Methods. We studied 402 individuals and classified them into four groups: healthy, obese, T2D obese, and T2D without obesity, from Guerrero, Southwestern Mexico. Blood levels of CRP, glucose, cholesterol, triglycerides, and leukocytes were measured. Genotyping was performed by PCR/RFLP, and the risk scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…This is an important topic because CRP levels may be related to CRP gene mutations. Previous studies demonstrated that CRP levels were associated with different CRP alleles and haploids . Our study showed that CRP levels were similar with and without CRP gene polymorphism.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is an important topic because CRP levels may be related to CRP gene mutations. Previous studies demonstrated that CRP levels were associated with different CRP alleles and haploids . Our study showed that CRP levels were similar with and without CRP gene polymorphism.…”
Section: Discussionsupporting
confidence: 74%
“…performed a large population study showing that the presence of a CRP minor allele was related to lower CRP levels in hypertensive patients. In a Mexican population, large sample studies by Martínez‐Calleja et al . showed that the CRP gene polymorphism was related to increased CRP levels and was a cardiovascular risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…Y. However, Martínez-Calleja et al (2012) showed that one of these SNPs (rs1130864) is directly related to BMI, and it is also known that there exists a negative association between higher levels of BMI and HDL (Shamai et al, 2011). Hence, these 3 SNPs may not all be valid instruments for causal effect estimation of CRP protein levels on HDL.…”
Section: Approaches Based On 2slsmentioning
confidence: 99%
“…Polymorphisms located in promoter regions, including rs2794521 (-717 A/G) of CRP gene, -572 C/G (rs1800796) of IL6 gene and -1031 T/C (rs1799964) of TNF gene, have been associated with T2DM risk [7,[9][10][11][12][13]. Several studies demonstrated a notable in uence of the rs2794521 polymorphism on CRP secretion [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated a notable in uence of the rs2794521 polymorphism on CRP secretion [14][15][16]. Alteration of CRP concentration may modify T2DM risk [5][6]9]. Similarly, the rs1800796 IL6 polymorphism was postulated to affect the expression of interleukin 6 [11,17] which can initiate insulin resistance and eventually T2DM [3].…”
Section: Introductionmentioning
confidence: 99%